Consensus clustering based on CT radiomics has potential for risk stratification of patients with clinical T1 stage lung adenocarcinoma - Hao Dong; Yang Li; Lingli Zhao; Lekang Yin; Xiaojun Guan; Xiaodan Ye; Xiaojun Xu (BMC Medical Imaging)
Abstract Background This study aimed to clinically risk-classify patients with clinical stage T1 LUAD based on consensus clustering of CT radiomics to help clinics provide personalized treatment strategies for patients with early stage LUAD. Materials Clinical, pathological and CT imaging data of patients who underwent surgical resection and pathologically confirmed lung adenocarcinoma from September 2018 to May 2021 were retrospectively analysed. The clinical and pathological information included age, gender, smoking history, tumor location, pathological subtype, infiltration level, lymph node metastasis (LNM), visceral pleural infiltration (VPI), lymphovascular invasion (LVI), spread through air space (STAS), Ki-67 proliferation index, and gene mutation information. Unsupervised consensus clustering analysis was performed based on the radiomic features of CT images to determine the optimal cluster values and evaluate the effect of consensus clustering. Patients were grouped according to the consensus clustering results, and compared with the histopathological characteristics of the tumors, genomic information and subgroup analyses were performed in invasive adenocarcinomas and sub-solid lesions. Results Totally 497 cases were determined to be classified into 2 clusters (optimal), with 258 (51.9%) cases in cluster 1 and 239 (48.1%) cases in cluster 2. There were statistically significant differences between cluster 1 and cluster 2 in micropapillary component, solid component, STAS, and Ki-67 proliferation index (p < 0.001), as well as statistically significant differences in LNM and VPI (p = 0.031 and 0.012 respectively). Additionally, micropapillary component, solid component, STAS, and Ki-67 proliferation index were also statistically different in subgroup analyses of invasive adenocarcinomas and sub-solid foci (p < 0.05). The clusters 1 and 2 were statistically different only in HER2 mutations (p < 0.001). Conclusion Consensus clustering based on CT radiomics can identify the associations of radiomic features between pathological risk factors and genomic features in clinical stage T1 lung adenocarcinoma, which can help clinical risk stratification of stage T1 lung adenocarcinoma patients. Clinical trial number Not applicable.